The water resources of Zielona Góra as an element of its sustainable development = Zasoby wodne Zielonej Góry elementem jej zrównoważonego rozwoju - Wróbel, Ireneusz; Lipnicki, Zygmunt (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of this paper is the presentation the water resources and water management as an example of Zielona Góra. In the paper it is shown that the water management should be recognized as the element of the sustainable development of the city. Economic activities in the city should be subordinated to the possibilities of the natural environment and should not disturb both the natural and the water balance.
Keywords: zasoby wodne; wody podziemne; Zielona Góra; water resources; underground water; water table; sustainable development